Analysis of the Productivity of Educational Expenditures and Their Impact on Human Development in Iraq - Imad Abdallah, zina; Mohammad Saloom , Taamem (Journal of Economics and Administrative Sciences, 2024)
Purpose : Analysis of the path of public spending on the education sector with an analysis of some human development indicators and the extent to which educational spending contributes to raising the level of human development for the period (2004-2023) in Iraq. Theoretical Framework: The current research addressed the study of the relationship between government spending in the education sector and the impact of that spending on human development, and the research problem focuses on the inefficiency of educational expenditures in Iraq and their limited impact on human development. Despite significant investments, challenges such as low literacy rates and poor educational outcomes persist. The study seeks to explore the reasons behind this disconnect, examining how funds are allocated and utilized. It aims to identify barriers that prevent these expenditures from effectively enhancing human capital and contributing to broader socio-economic development. Design/Methodology/Approach: The researcher relied on a mixed approach that combines the descriptive analytical approach to draw the theoretical framework for government spending, the education sector, and human development indicators, in addition to the quantitative standard approach to identify the impact that government spending in the education sector plays on the level of human development. For this purpose, the E-Views10 program was used, and the data extended for the period from 2004-2023. Findings: The results of the statistical analysis showed that the standard model is free from all statistical problems and gives accuracy to the model. Research, Practical & Social implications: The current research contributes to clarifying the role of government expenditures on the sector and its reflection in the development of some human development indicators in Iraq. Originality/Value: The originality of the current research is evident in that it contributes to bridging the research gap between government spending in the education sector and the impact of this spending on human development in developing countries. The research results reached in the standard aspect have shown that education contributes to enhancing human development, so these results add important evidence to the relevant literature.